Inferring Zonal Wind Profiles in the Equatorial Electrojet From Coherent Scatter - Hysell, D.L. (2022)
Zonal wind estimates in the equatorial electrojet derived from coherent scatter echoes, specular meteor trail echoes, and optical limb scans are compared. While the three techniques exhibit broad overall agreement, significant differences in the results of the three techniques appear. The differences can be attributed in large part to horizontal inhomogeneity in the winds and the dissimilar averaging kernels of the three techniques.